2002
DOI: 10.1525/sop.2002.45.3.267
|View full text |Cite
|
Sign up to set email alerts
|

How Cohorts, Education, and Ideology Shaped a New Sexual Revolution on American Attitudes toward Nonmarital Sex, 1972–1998

Abstract: Data from the 1972–98 General Social Surveys document changes in attitudes toward premarital, extramarital, homosexual, and teenage sex. This analysis demonstrates the liberalizing effect of cohort succession but also finds intracohort change in attitudes as the birth cohorts age. Intracohort change dominated recent dramatic declines in disapproval of homosexuality. As theories of individualism and postmaterialism suggest, higher education, secularism, and relative income are associated with greater tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(157 citation statements)
references
References 26 publications
5
147
2
3
Order By: Relevance
“…Similar to other attitudes regarding controversial subjects in the personal sphere, such as euthanasia (Jaspers, Lubbers and De Graaf 2007) and sexual intercourse outside marriage (Treas 2002), studies have reported a prolonged decline in disapproval of homosexuality over the last decades, in Europe ( Van de Meerendonk and Scheepers 2004), as well as in other Western countries (Inglehart 1989). These changes in attitudes over time are, however, more complex than might seem at first glance.…”
Section: Trends Over Timementioning
confidence: 71%
See 2 more Smart Citations
“…Similar to other attitudes regarding controversial subjects in the personal sphere, such as euthanasia (Jaspers, Lubbers and De Graaf 2007) and sexual intercourse outside marriage (Treas 2002), studies have reported a prolonged decline in disapproval of homosexuality over the last decades, in Europe ( Van de Meerendonk and Scheepers 2004), as well as in other Western countries (Inglehart 1989). These changes in attitudes over time are, however, more complex than might seem at first glance.…”
Section: Trends Over Timementioning
confidence: 71%
“…During the last decades, a prolonged decline in disapproval of homosexuality has been observed, in Europe and other industrialized nations (Loftus 2001;Treas 2002). The apparent decline in disapproval of homosexuality among natives in Western countries, might, however, not be a simple change in attitudes over time among all individuals, but seems to be largely attributable to cohort replacement (Inglehart 2008;Jaspers, Lubbers and De Graaf 2007;Meeusen and Hooghe 2012;Van de Meerendonk and Scheepers 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps people came to represent sexual orientation as 'innate' and this facilitated a broad change in their attitudes towards homosexuality (Sheldon, Pfeffer, Jayaratne, Feldbaum, & Petty, 2007;Wood & Bartkowski, 2004;); however, the mismatch hypothesis suggests that the causation may have traveled in the reverse direction. For example, cohort effects may have improved attitudes towards homosexuality (Andersen & Fetner, 2008;Treas, 2002) and this may have caused same-sex attraction to appear more essence-disclosing ('innate'). Thus, a tendency to represent the true self as virtuous may also help to explain the continued attraction of psychotherapies aimed at 'reorienting' nonheterosexuals (Dean Byrd, Nicolosi, & Potts, 2008;Haldeman, 2002).…”
Section: Why It May Be Better Not To Believe People Are Virtuousmentioning
confidence: 99%
“…Indeed, over the past few decades emerging adults have also become increasingly accepting of premarital sexual activity within a committed relationship (Martin et al 2001;Treas 2002;Wells and Twenge 2005). Taking a developmental perspective Shulman and Seiffge-Krenke (2001), argue that adolescent relationships will naturally progress to include more sexual activity as a couple develops more characteristics of a true dyadic relationship.…”
Section: Literature Reviewmentioning
confidence: 99%